Archaeology with art - Theoretical Archaeology Group (England). (Oxford)
xx, 176 sayfa
Keywords: “Archaeology with Art is the result of a 2013 Theoretical Archaeology Group (TAG) conference session that aimed to merge the perspectives of artists and archaeologists on making art. It explores the relationship between archaeology and art practice, the interactions between materials and practitioners, and the processes that result in the objects and images we call 'art'. The book offers new approaches to the study of creative practices in archaeology, ranging from experimental investigations to philosophical explorations and contains a diverse set of papers that use insights from contemporary art practice to examine the making of past artworks.” --